Quality issues related to the design and construction stage of a project in the Indian construction industry. Issue 2 (2nd September 2021) - Khan, Sharmin; Saquib, Mohammad; Hussain, Anwar
Abstract : Purpose: Quality in the construction industry is an important issue yet ignored during the initial stages of the life cycle of a project, that is, the design and construction stage. The contribution of stakeholders, especially the architects is generally suspended though it has huge significance in terms of cost and time related to quality. This research endeavors to examine the issues related to the design and construction stages of the project from architects' purview, to understand the relative importance of these issues in the Indian construction industry. Design/methodology/approach: The study of qualitative data conducted formed a basis for online quantitative data collection that was further analyzed with the help of cross-tabulation and multiple correspondence analysis methods. Findings: The study concludes that the budget of a project is a corresponding factor related to quality concern for architects. The study also established that the quality issues corresponding to high budgets are closely related to the construction stage and are identified as preparation of checklist, and bidding process of hiring the contractor on the lowest bid. Research limitations/implications: The study is limited to analyzing the perspective of architects; however, other stakeholders of the construction industry may represent a different opinion. Practical implications: This research emphasizes the importance of the client's role, and need for integration and coordination among stakeholders in the construction industry for effective quality control and management. Originality/value: The research presents an exhaustive literature review on quality issues and its importance with respect to cost implications, standard practices, sustainability and the life cycle of the project.